Social representations of gay politicians. Daniel Al Banas Delfin. - Delfin, Daniel Al Banas
This study explored the social representations of social groups in Iloilo regarding gay politicians by determining the elements of their representations and the social meanings of these elements. The study had two parts, using both quantitative and qulitative research designs. For both parts, four social groups were identified namely: general voting public, politicians, LGBT community and church leaders. The first part of the study consisted of forty respondents from each social group who answered questionnaires asking them about the three first things they thought of when they hear the word 'gay politician'. Elements were analyzed through the Hierarchical Evocation method. For the second part, focus group discussions were conducted with seven respondents from each social group. They were asked about their opinions regarding gay politicians and were allowed discuss the context of their responses. Thematic analyses were then conducted. Results from the questionnaire revealed the absence of a unifying central core element among all groups. However, elements identified in their responses were essentially similar and differed only in the degree of salience given to them by each group. Results from the focus group discussions revealed that the difference in major elements held by groups is because of where groups anchored their beliefs about the social object. It was also revealed that three out of the four groups were open to voting for gay politicians but all four ultimately assess Iloilo as still not being ready to ahve gay politician in office.